An Ecological Assessment for Water Quality of Some Water Bodies in Koysenjaq-Erbil, Iraq. - Toma, Janan Jabbar; Shekha, Yahya Ahmad; Al-Barzingy, Yadi Omar Mustafa (Al-Nahrain Journal of Science, 2018)
Water `assessment and algal composition study was conducted near Koysenjaq district for nine sites including (4) springs and (5) streams. Monthly water samples collected from April-2013 to March-2014 and 15 physico-chemicals parameters and algal content were analyzed. Generally, pH of water tend to be in alkaline side of neutrality. Mean values of electrical conductivity ranged between 272-441µs.cm-1 in January and July respectively. Total hardness extended from hard to very hard water. Cation arranged in order as follows: Ca> Mg>Na>K. Higher mean value of ammonium recorded in site 6 was 14.8 µg N.NH3.l-1, and minimum value of nitrite was 0.68µg N.NO2.l-1 in site 6. Mean values of phosphate ranged between (0.82-4.5µg P-PO4.l-1). Highest value of dissolved oxygen were observed in sites 7, 8 and 9, while the minimum value of biochemical oxygen demand recorded in site 2 was 0.7mg.l-1. A total 73 species of algal species were identified of which belong to Bacillariophyceae (25 species), Cyanophyceae (23 species), Chlorophyceae (16 species), Euglenophyceae (4 species), Charophyceae and Xanthophyceae (2 species for each one) and 1 species belong to Rhodophyceae. Multivariate statistical techniques results revealed that water quality of the monitored water bodies were influenced by many pollution sources including the geological formation of the area, agricultural activities and effluent of domestic sewage water.